Bt cotton area contraction drives regional pest resurgence, crop loss, and pesticide use. Issue 2 (18th October 2021) - Lu, Yanhui; Wyckhuys, Kris A. G.; Yang, Long; Liu, Bing; Zeng, Juan; Jiang, Yuying; Desneux, Nicolas; Zhang, Wei; Wu, Kongming
Summary: Genetically‐modified crops expressing Bacillus thuringiensis (Bt) proteins have been widely cultivated, permitting an effective non‐chemical control of major agricultural pests. While their establishment can enable an area‐wide suppression of polyphagous herbivores, no information is available on the impact of Bt crop abandonment in entire landscape matrices. Here, we detail a resurgence of the cosmopolitan bollworm Helicoverpa armigera following a contraction of Bt cotton area in dynamic agro‐landscapes over 2007–2019 in North China Plain. An 80% reduction in Bt cotton was mirrored in a 1.9‐fold increase of ambient H. armigera population levels, culminating in 1.5–2.1‐fold higher yield loss and a 2.0–4.4‐fold increase in pesticide use frequency in non‐Bt crops (i.e. maize, peanut, soybean). Our work unveils the fate of herbivorous insect populations following a progressive dis‐use of insecticidal crop cultivars, and hints at how tactically deployed Bt crops could be paired with agro‐ecological measures to mitigate the environmental footprint of crop production.